Signal-to-Noise Performance Evaluation of a New 12-Bit Digitizer on a Time-of-Flight Mass Spectrometer. Issue 1 (February 2015) - Hondo, Toshinobu; Kawai, Yousuke; Toyoda, Michisato
Rapid acquisition of time-of-flight (TOF) spectra from fewer acquisitions on average was investigated using the newly introduced 12-bit digitizer, Keysight model U5303A. This is expected to achieve a spectrum acquisition 32 times faster than the commonly used 8-bit digitizer for an equal signal-to-noise (S/N) ratio. Averaging fewer pulses improves the detection speed and chromatographic separation performance. However, increasing the analog-to-digital converter bit resolution for a high-frequency signal, such as a TOF spectrum, increases the system noise and requires the timing jitter (aperture error) to be minimized. We studied the relationship between the S/N ratio and the average number of acquisitions using U5303A and compared this with an 8-bit digitizer. The results show that the noise, measured as root-mean-square, decreases linearly to the square root of the average number of acquisitions without background subtraction, which means that almost no systematic noise existed in our signal bandwidth of interest (a few hundreds megahertz). In comparison, 8-bit digitizers that are commonly used in the market require 32 times more pulses with background subtraction.